Copper Deficiency in Sheep with High Liver Iron Accumulation - Isadora Karolina Freitas de Sousa; Antonio Humberto Hamad Minervino; Rejane dos Santos Sousa; Dowglish Ferreira Chaves; Herbert Sousa Soares; Isabella de Oliveira Barros; Carolina Akiko Sato Cabral de Araújo; Raimundo Alves Barrêto Júnior; Enrico Lippi Ortolani (Veterinary Medicine International)
An outbreak of enzootic ataxia among sheep raised in the northeastern region of Brazil is described. Copper (Cu) deficiency was diagnosed in a herd of 56 sheep, among which five presented characteristic clinical symptoms of enzootic ataxia. The symptoms began 30 days after birth, with a clinical condition that included locomotion difficulty, limb ataxia, tremors, and continual falls. Liver biopsies were performed and blood was collected to determine hepatic and plasmatic Cu, iron (Fe), and zinc (Zn) concentration, respectively. The laboratory results showed that the animals presented low copper concentrations in the plasma and liver, without difference between the clinically healthy animals and those affected by enzootic ataxia. Even after supplementation with adequate Cu levels had been recommended, it was found on a new visit to the farm four months later that one animal still presented a clinical condition and that the hepatic Cu levels of the herd had not risen. Despite the low copper content of the diet, the high hepatic Fe levels found suggest that antagonism due to this element may have been an important factor in triggering copper deficiency in these animals, and thus, additional copper supplementation may be necessary for these animals.